PENGEMBANGAN BAHAN AJAR INTERAKTIF UNTUK PEROLEHAN KETERAMPILAN PADA MATERI LINGKARAN - Ulvi Ulya; Dede Suratman; Asep Nursangaji (UNIVERSITAS TANJUNGPURA, 2020)
This research aims to determine the feasibility of interactive teaching materials that are developed, and how intellectual skills of students after using teaching materials that are developed. The research method used is descriptive. The subjects of this research were 24 students from class XI SMP Islam Bawari Pontianak. The data source of this research were the student test answers sheet, and the validation sheet for the feasibility of interactive teaching materials. The results showed that interactive teaching materials were declared to be very valid, refer to material experts and media experts. The students' intellectual skills of relationship the central angle with length of arc is 58.33% in the sufficient category. The students' intellectual skills of relationship the central angle with area of circle sector is 50% in the sufficient category. The students' intellectual skills of solve problems related to the central angle, inscribed angle, length of arc, and area of circle sector, and its relationship is 20.83% in the low category.Keywords: Circles, Intellectual Skills, Interactive Teaching Materials